Intoxicação espontânea por Senecio brasiliensis (compositae) em ovinos - Ilha, Marcia Regina da Silva (2001)
An outbreak of spontaneous Senecio brasiliensis poisoning in grazing sheep in the county of Mata, Rio Grande do Sul, southern Brazil, is described. The disease occurred in one farm in middle January 1997. Fifty-one out of ninety-four sheep were affected and fifty animals (53.2%) died. This flock of sheep had been grazing for approximately 7 months (from June 1996 to January 1997) in paddocks heavily infested with S. brasiliensis. Clinical signs included photodermatitis, progressive emaciation, apathy, weakness, neurological signs such as drownsiness, aimless walking and unsteady gait, jaundice and hemoglobinuria. There was amelioration of the skin lesions in those sheep that developed hepatogenous photosensitization. Main necropsy findings in 9 sheep included small, firm, yellowish-brown (tan) or greenish liver with few to numerous small, yellowish, well-circunscribed nodules measuring up to 3 mm in diameter randomly scattered throughout the hepatic parenchyma.There was also marked distension of the gallbladder which contained large amounts of inspissated, dark green bile and straw-colored cavitary effusions (hydropericardium and ascitis). Five sheep developed lethal acute hemolytic crisis secondary to massive release of copper accumulated in the liver into the blood stream (hepatogenous chronic copper poisoning). Apart from the aforementioned liver lesions, other gross findings in those animals included severe and diffuse jaundice, dark brown urine (hemoglobinuria) and swollen, friable, finely stippled or diffusely dark kidneys. The main histopathological findings included hepatomegalocytosis, biliary ductal proliferation (bile duct hyperplasia) and moderate periportal fibrosis. The portal triads were infiltrated with variable numbers of mononuclear cells. There was heavy accumulation of brownish pigment in macrophages identified as ceroid or copper with PAS and rhodanine stainings, respectively. Those ceroid and copper-laden macrophages were scattered on the remnant hepatic parenchyma or formed small aggregates in the portal triads. Main histopathological lesions in the kidneys of 5 sheep that developed fatal hepatogenous chronic copper poisoning included tubular nephrosis, accumulation of hemoglobin and hemosiderin in epithelial tubular cells and hemoglobin casts (hemoglobinuric nephrosis). Morphological evidence of hepatic encephalopathy included spongy degeneration (status spongiosus) of the cerebral white matter. Ultrastructural changes in the liver of affected sheep included degenerative hepatocellular changes of varying severity. There was accumulation of numerous lipid droplets in the cytoplasm of the hepatocytes and lysosomes containing substances of high electron-density that corresponded to ceroid-lipofuscin in most of the cases. In addition, there was mild swelling of the rough endoplasmic reticulum and moderate hyperplasia of the smooth endoplasmic reticulum in some areas of the cytoplasm of the hepatocytes. Proximal convoluted tubular epithelial cells showed intracellular edema and a variety of mitochondrial degenerative changes. These included disarrangement and breakup of cristae, finely granular matrix, accumulation of lipid globules and rupture of the membranes in a few cases. Many epithelial tubular cells displayed substances of high electron-density within lysosomes.Chemical analysis of copper in liver and kidney samples of affected sheep revealed high concentrations varying from 369 ppm to 1248 ppm in the liver and ranging from 152 ppm to 687 ppm in the kidneys (dry matter). The diagnosis was based on epidemiological data, clinical signs, necropsy findings, histological lesions and laboratory data.